2019
DOI: 10.1007/s10921-019-0643-0
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Dependent Magnetic Flux Leakage: Finite Element Modelling Simulations Versus Experiments

Abstract: Assessing the effect of defect induced stresses on magnetic flux leakage (MFL) signals is a complicated task due to nonlinear magnetomechanical coupling. To facilitate the analysis, a multiphysics finite elemental simulation model is proposed based on magnetomechanical theory. The model works by quasi-statically computing the stress distribution in the specimen, which is then inherited to solve the nonlinear magnetic problem dynamically. The converged solution allows identification and extraction of the MFL si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The stress effect has been studied by many researchers [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. The properties of ferromagnetic materials change with the loading stress due to the magneto-mechanical coupling, thus the MFL signal also changes with the stress.…”
Section: Factors Influencing Mfl Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…The stress effect has been studied by many researchers [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. The properties of ferromagnetic materials change with the loading stress due to the magneto-mechanical coupling, thus the MFL signal also changes with the stress.…”
Section: Factors Influencing Mfl Signalmentioning
confidence: 99%
“…The properties of ferromagnetic materials change with the loading stress due to the magneto-mechanical coupling, thus the MFL signal also changes with the stress. Y. Wang proposed a multi-physics simulation model to study the change in MFL signal with stress and showed that the peak-to-peak amplitude of the normalized MFL signal decreases with an increase in stress [ 80 ]. Mandal showed that the circumferential bending stress changes the magnetic easy axis of the pipe and thus reduces the MFL signal [ 81 ].…”
Section: Factors Influencing Mfl Signalmentioning
confidence: 99%
“…When a ferromagnetic material is subjected to the action of elastic stress ( σ ) in an applied magnetic field ( H ), the magnetization ( M ) of the material is dominated by an effective field, H e , which can be expressed as [ 12 , 21 , 27 ] where H σ represents the equivalent magnetic field induced by the stress. This equivalent field results from the magnetoelastic coupling and is given by where ν is the Poisson’s ratio, θ is the angle between the stress axis and the direction of H σ , and λ is the bulk magnetostriction, whose partial differential with respect to magnetization is determined by fitting λ ≈ a + bM 2 [ 13 , 28 ] from the experiment. When the direction of stress is parallel to that of magnetization, Equation (19) can be rewritten as …”
Section: The Effect Of Temperature On Magnetic Barkhausen Noisementioning
confidence: 99%
“…The quantization of the pipeline MFL signal is the ultimate goal of MFL detection [ 14 ]. Most of the quantization methods are to carry out a large number of calibrations of experimental data [ 15 , 16 ], but the failure to take into account the complex situation in the pipeline will lead to poor accuracy and impracticality of the quantization method; therefore, the quantization of the theoretical model has become a hot research topic [ 17 , 18 ]. Under the influence of the internal pressure of the medium and the surrounding environment, there is a large stress concentration area at the defect [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%